Outcome and predictors for smoking cessation in a quit smoking clinic - Zainal Abidin, Muhammad Adil; Kadi @ Shahar, Hayati; Abdul Manaf, Rosliza (Department of Community Health, Universiti Kebangsaan Malaysia Medical Centre, 2017)
Introduction: Smoking is one of the addiction problems that needs an effective intervention. Smoking cessation studies have shown the promising result, but the central issue was to prevent relapse. A retrospective cohort study was conducted at Quit Smoking Clinic in Klinik Kesihatan Tanglin, Kuala Lumpur to determine the outcome and predictors of smoking cessation. Methods: A cohort of 770 smokers attended the clinic between the year 2008 and 2015 was selected through simple random sampling. Smokers were defined as current smokers while smoking abstinence is defined as cessation for more than 6 months and relapse as any smoking episode even a puff since the quit date. Results: The majority were Malays, Muslims and had at least secondary education. The mean age of smoking initiation was 17.6 years old. The majority of the respondent smokes between 11 to 20 sticks per day and had a higher nicotine dependence score (43.0%). The smoking cessation outcome was good with 52.5% of the respondent abstained from smoking at 6 months. The predictors for smoking cessation were numbered of the quit attempt (1 to 10 times) (AOR = 1.582, 95% CI = 1.012-2.472) and pharmacotherapy (aOR = 0.711, 95% CI=0.511-0.989). Conclusions: More frequent follow-up was essential during the first 6 month period to enhance not only medication compliance but also a motivational aspect to smokers to maintain cessation. Emphasis should also be made for smokers who make first quit attempt.